La situación de los portazgos, pontazgos y barcajes de la provincia de León en el siglo XVIII según los informes del intendente - Bartolomé Bartolomé, Juan Manuel (Estudios humanísticos. Geografía, historia y arte, 1999)
We've carried out this research work in order to study some mesures performed during the Enlinghtenment. Politicians wanted to improve the transport of people and goods by road and river in León, which was hindered by the taxes